The Effect of Rainfall Anomalies on the Productivity of Clove Plants (Syzygium aromaticum) and Management Strategies in Southeast Sulawesi - Ardiansa, Feling; Sabaruddin, Laode; Alam, Syamsu (Publisher Cv. Inara, 2025)
Climate change has caused rainfall anomalies that have an impact on decreasing the productivity of clove plants (Syzygium aromaticum). This study aims to analyze extreme rainfall anomalies in North Buton Regency and Kolaka Regency, assess its impact on the productivity of clove plants (Syzygium aromaticum), and formulate management strategies that can be applied to increase crop yields. The method used is a quantitative descriptive approach with linear regression analysis to determine the relationship between rainfall and clove productivity. The research population is clove farmers in North Buton Regency and Kolaka Regency, with a sample of three farmers in each village where the research is located. Rainfall data was obtained from the Betoambari Bau-Bau Meteorological Station and the Sangia Nibandera Kolaka Meteorological Station during the 2009–2023 period, while clove crop productivity data was obtained from farmer surveys and reports from the Central Statistics Agency. The results of the study show that North Buton Regency has an average annual rainfall of 1,971 mm with slightly wet climate characteristics (Type C), while Kolaka Regency has an average annual rainfall of 1,973 mm with wet climate characteristics (Type B). Based on the evaluation of the suitability of the rainfall land, it is included in the S1 category (very suitable). Regression analysis showed that rainfall had a less significant relationship with the productivity of clove plants. The results of the regression analysis showed that the determination coefficient (R2) of North Buton Regency was 12.59% and Kolaka Regency was 14.21%. Recommended management strategies to deal with rainfall anomalies in Kolaka Regency include improving drainage systems, soil management and conservation, and environmental sanitation. Meanwhile, in North Buton Regency, it includes the provision of irrigation, the use of mulch and the provision of organic matter.